Effects of reduced pH and elevated pCO 2 on sperm motility and fertilisation success in blood clam, Tegillarca granosa - Wei Shi; Xinguo Zhao; Yu Han; Cheng Guo; Saixi Liu; Wenhao Su; Yichen Wang; Shanjie Zha; Xueliang Chai; Wandong Fu; Huicheng Yang; Guangxu Liu (New Zealand Journal of Marine and Freshwater Research, 2017)
Although it has been shown that ocean acidification generally has a negative impact on fertilisation success of broadcast spawning marine organisms, whether induced fertilisation success reduction is a consequence of elevated p CO 2 or decreased pH remains unclear. Therefore, the impacts of HCl‐ and CO 2 ‐induced acidified seawater on sperm motility and gametes fertilisation capability of a broadcast spawning bivalve species, Tegillarca granosa were investigated in the present study. The results showed that the fertilisation capability of both gametes was significantly reduced in either HCl‐ or CO 2 ‐acidified seawater. In addition, significant impacts on sperm motility were observed in the group exposed to CO 2 ‐acidified seawater, suggesting that this parameter is sensitive to p CO 2 instead of solely pH value. The differences between the two seawater acidification manipulating methods may be due to the intrinsic difference in diffusion capability of CO 2 and protons.